Pemex: oil price and financial management in the context of elevated fiscal burden - Tacuba, Angélica (2022)
Purpose: The article analyzes how oil price fluctuations are reflected in the management of Petróleos Mexicanos (Pemex) based on its balance sheet (BS) and particularly how oil price fluctuations affect Pemex's corporate income. Design/methodology/approach: The author uses a vector auto-regressive (VAR) model with seven variables for the period 1977–2019. The first variable is the oil price and the others belong to Pemex's BS: total income, sales revenue, operating costs, investment, payment of taxes, duties and contributions (TDC) and the payment of interest on debt. Findings: The results show that in an environment of elevated fiscal burden that is of an excessive payment of tax by Pemex to the state, the price increases positively affected the income obtained from sales, but that surplus is used primarily to finance the fiscal expenses coming from the TDC, which is associated with the production and commercialization of hydrocarbons; physical and financial investment is disconnected from the evolution of price. Under a fiscal scheme that extracts, on average, 98.46% of Pemex's income, investment is not a priority. Practical implications: The findings of the research have important implications for Mexico's energy policy because of affecting the long-term financial and productive sustainability of Pemex. Originality/value: First, the study contributes to the literature on oil prices in Mexico by analyzing Pemex's fiscal burden from a corporate finance perspective, an area in which there are few rigorous studies. Second, the study contributes by providing quantitative support for the relationship between oil prices and BS variables through the VAR model.